ASSOCIATION BETWEEN DURATION OF SCREEN TIME AND PSYCHOSOCIAL PROBLEMS AMONG ADOLESCENTS (10–19 YEARS): A CROSS-SECTIONAL STUDY (Asian Journal of Medical Research and Health Sciences, 2026)
Background: Over the previous decade, adolescents' use of digital devices has expanded rapidly. Excessive recreational screen time has been associated with emotional, behavioral, and social problems. Objective: To ascertain the relationship between the amount of time spent on screens each day and psychological issues in teenagers between the ages of 10 and 19. Methods: 400 teenagers chosen by multistage random sampling participated in a cross-sectional survey carried out in a school. Screen time was divided into three categories: less than two hours, two to four hours, and more than four hours per day. The Strengths and Difficulties Questionnaire (SDQ) was used to evaluate psychosocial issues. ANOVA, multivariate logistic regression, and the chi-square test were used to examine the data. Results: Thirty-eight percent of interviewees said they used screens for more than four hours per day. Adolescents exposed for more than four hours per day had mean total SDQ scores that were considerably higher (21.4 ± 5.2) than those exposed for less than two hours per day (14.8 ± 4.6) (p